Efficiency, capacity and democratic deficits. Arguments for and against municipal amalgamations in Iceland for 70 years - Grétar Þór Eyþórsson (Veftímaritið Stjórnmál og stjórnsýsla, 2014)
This article deals with analyzing the arguments which have been used in the debates in Iceland about municipal amalgamations for a period of seventy years. Both the arguments of the pre- side and the against- side are analysed. The frame for analysis used are definitions on efficiency, capacity and democracy in connection with the question of municipal size, done by the Danish political scientists Ulrik Kjær and Poul Erik Mouritzen. The main results of the analysis is that a) efficiency, b) administrative capacity, c) functional- and developmental capacity, d) implementation capacity and e) the ability to adapt to socio-economic changes, are the main arguments used by the pre- side, especially the ones about efficiency and administrative capacity. The most significant arguments from those against amalgations have been arguments on democracy, a) negative consequences for democracy by territory and by functions and b) negative consequences for democracy due to the loss of important elements of participation and closeness in the small context.